ASPREE-D: Aspirin for the prevention of depression in the elderly - Berk, M.; Woods, R.; Nelson, M.; Shah, R.; Reid, Christopher; Storey, E.; Fitzgerald, S.; Lockery, J.; Wolfe, R.; Mohebbi, M.; Murray, A.; Kirpach, B.; et al. (Cambridge University Press, 2016)
Copyright © International Psychogeriatric Association 2016. Background:: Not only is depression associated with increased inflammation but inflammation is a risk factor for the genesis of depression. Many of the environmental risk factors for depression are transduced through inflammatory signaling. Anti-inflammatory agents show promise for the management of depression in preclinical, epidemiological, and early clinical studies. This opens the door to the potential for anti-inflammatory agents to treat and prevent depression. There are no evidence-based pharmacotherapies for depression prevention. Method:: ASPREE-D, aspirin in the prevention of depression in the elderly, is a sub study of ASPREE, which explores the potential of aspirin to prevent a range of inflammation related disorders in the elderly. With a sample size of 19,114, and a duration of 5 years, this placebo controlled study will be one of the largest randomized controlled trials in psychiatry and will provide definitive evidence on the ability of aspirin to prevent depression. Results:: This paper presents the rationale for the study and presents a summary of the study design. Conclusions:: ASPREE-D may not only define novel therapy but will provide mechanistic proof of concept of the role of inflammation in depression.